Smart Trends in Computing and Communications Proceedings of SmartCom 2021 - Zhang, Yu-Dong; Senjyu, Tomonobu; So-In, Chakchai; Joshi, Amit (Lecture Notes in Networks and Systems, 2022)
XXVIII, 762 p. 395 illus., 320 illus. in color.